1955
DOI: 10.1021/ja01627a041
|View full text |Cite
|
Sign up to set email alerts
|

Mono- and Bis-(1-aziridinyl)-s-triazines

Abstract: Vol. 77 after water-insoluble material was removed by filtration. The yield of triethylenemelamine was 86%. Yields were about 5% lower when technical grade cyanuric chloride was used.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

1955
1955
2000
2000

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(4 citation statements)
references
References 1 publication
0
4
0
Order By: Relevance
“…Table I lists the compounds obtained and applied in pure form (functionality as determined by the method of Schaefer [11] found to he 90% of the calculated value or higher). ~I~ahlc I 1 lists the compounds which could not 1e purified and were applied in erucIc form (functionality approximately 80% of the calculated value).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Table I lists the compounds obtained and applied in pure form (functionality as determined by the method of Schaefer [11] found to he 90% of the calculated value or higher). ~I~ahlc I 1 lists the compounds which could not 1e purified and were applied in erucIc form (functionality approximately 80% of the calculated value).…”
Section: Methodsmentioning
confidence: 99%
“…Table 11). Ag~iiii, as before, about two-thirds of the assistants showed a M<'~//:'r bias relative to the stated diameter of the top used.…”
mentioning
confidence: 99%
“…The reaction of aziridines ( R = H , triazinyl) with thiosulfate yields S-alkyl thiosulfates (131,132), which are known as Bunte salts (133).…”
Section: Reaction With Nitrogenmentioning
confidence: 99%
“…It has been found that the usual procedures for (1) (a) We were informed of this work by Dr. M. L. Crossley who had made samples of triethylenemelamine available for testing; (b) M. R. Lewis and M. L. Crossley, Arch. Biochem., 26, 319 (1950);…”
mentioning
confidence: 99%